Mesenchymal Stem Cell-Derived Extracellular Vesicles: Challenges in Clinical Applications - Gowen, Austin; Shahjin, Farah; Chand, Subhash; Odegaard, Katherine E.; Yelamanchili, Sowmya V. (Frontiers in Cell and Developmental Biology, 2020)
Stem cell therapy has garnered much attention and application in the past decades for the treatment of diseases and injuries. Mesenchymal stem cells (MSCs) are studied most extensively for their therapeutic roles, which appear to be derived from their paracrine activity. Recent studies suggest a critical therapeutic role for extracellular vesicles (EV) secreted by MSCs. EV are nano-sized membrane-bound vesicles that shuttle important biomolecules between cells to maintain physiological homeostasis. Studies show that EV from MSCs (MSC-EV) have regenerative and anti-inflammatory properties. The use of MSC-EV, as an alternative to MSCs, confers several advantages, such as higher safety profile, lower immunogenicity, and the ability to cross biological barriers, and avoids complications that arise from stem cell-induced ectopic tumor formation, entrapment in lung microvasculature, and immune rejection. These advantages and the growing body of evidence suggesting that MSC-EV display therapeutic roles contribute to the strong rationale for developing EV as an alternative therapeutic option. Despite the success in preclinical studies, use of MSC-EV in clinical settings will require careful consideration; specifically, several critical issues such as (i) production methods, (ii) quantification and characterization, (iii) pharmacokinetics, targeting and transfer to the target sites, and (iv) safety profile assessments need to be resolved. Keeping these issues in mind, the aim of this mini-review is to shed light on the challenges faced in MSC-EV research in translating successful preclinical studies to clinical platforms.